Pengaruh Kepercayaan Pelanggan Dan Ketersediaan Produk Terhadap Keputusan Pembelian Pada Toko Beras Grosir Puri Boh Hate di Depok - Zelin Ferdias Capriati; Sahwa Nindi Fitriyani (Journal of Innovative and Creativity, 2025)
The purpose of this study is to determine the influence of customer trust (X1) and product availability (X2) on purchase decisions (Y) at the Puri Boh Hate Wholesale Rice Shop in Depok. This study uses a quantitative method that is associative. The sampling technique used the Non-probability sampling method purposive sampling with the Slovin formula, so that a sample of 99 respondents was obtained. Data analysis techniques include validity test, reality test, classical assumption test, multiple linear regression, t test and f test. The results of the t-test showed that the customer trust variable (X1) had a t-count value (12.135) > t-table (1.661) and a significance value (0.000) < 0.05 which means that customer trust has a significant effect on purchase decisions. The results of the product availability variable (X2) test had a t-count value (7.895) > t-table (1.661) and a significance value (0.000) < 0.05 which means that product availability has a significant effect on purchase decisions. The results of the f-test showed an f-calculated value (77.245) > f-table (3.94) and evidence of significance value (0.000) < 0.05 which means that the variables of customer trust and product availability simultaneously affect the purchase decision. Therefore, it can be concluded that HO3 is rejected and Ha3 is accepted, meaning that there is a simultaneous significant influence between customer trust and product availability on purchase decisions.